2021
DOI: 10.1007/s00163-021-00365-w
|View full text |Cite
|
Sign up to set email alerts
|

266 Fuzzy front-end studies: current state and future directions for new product development

Abstract: Abstract266 fuzzy front-end (FFE) studies in the new product development (NPD) sector were examined. The studies were selected using a bibliometrics method, and chronologically and statistically examined with ten criteria divided into two dimensions. The first dimension is associated with overall attributes of the FFE, consisting of six criteria: the study taxonomy, model type, NPD speed, NPD attributes, model characteristic, and model structure. The second dimension is relevant to the FFE performance structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 148 publications
2
14
0
Order By: Relevance
“…Probably due to the youth of engineering design as a research discipline, the number of papers devoted to literature reviews in these fields is still sparse. From the few reviews found, most refer to particular aspects of engineering design: such as inspiration and fixation (Crilly 2019); sustainability (Coskun et al 2015); user value (Boztepe 2007); Alzheimer and play experience (Anderiesen et al 2015); performance in industrial design (Candi and Gemser 2010); relation between creativity, functionality, and aesthetics (Han et al 2021); fuzzy front-ends for product development (Park et al 2021); surrogate models and computational complexity (Alizadeh et al 2020); smart design (Pessôa and Becker 2020); design and poverty (Jagtap 2019); mass customization (Ferguson et al 2014); product stigma (Schröppel et al 2021); uncertainty (Han et al 2020); decision-making methods (Renzi et al 2017); modular product design (Bonvoisin et al 2016); or product-service systems (Vasantha et al 2012).…”
Section: Relation To Other Surveysmentioning
confidence: 99%
“…Probably due to the youth of engineering design as a research discipline, the number of papers devoted to literature reviews in these fields is still sparse. From the few reviews found, most refer to particular aspects of engineering design: such as inspiration and fixation (Crilly 2019); sustainability (Coskun et al 2015); user value (Boztepe 2007); Alzheimer and play experience (Anderiesen et al 2015); performance in industrial design (Candi and Gemser 2010); relation between creativity, functionality, and aesthetics (Han et al 2021); fuzzy front-ends for product development (Park et al 2021); surrogate models and computational complexity (Alizadeh et al 2020); smart design (Pessôa and Becker 2020); design and poverty (Jagtap 2019); mass customization (Ferguson et al 2014); product stigma (Schröppel et al 2021); uncertainty (Han et al 2020); decision-making methods (Renzi et al 2017); modular product design (Bonvoisin et al 2016); or product-service systems (Vasantha et al 2012).…”
Section: Relation To Other Surveysmentioning
confidence: 99%
“…Activities associated with front-end design phases, including problem definition, requirements and specifications development, and concept generation, are often described as ambiguous and ill-defined (Cooper 1988;Sanders & Stappers 2008;Park, Han & Childs 2021). Front-end design involves developing a deep understanding of the problem, which is accomplished through iteration of both the problem definition and potential solutions, defined as problem-solution co-evolution (Murphy & Kumar 1997;Dorst & Cross 2001;Dorst 2019).…”
Section: Front-end Design and Requirements Elicitationmentioning
confidence: 99%
“…During frontend design, the iterative nature of problems and solutions is evident through evolving product requirements, which define the design problem and focus designers' efforts. Research has tied many product failures to errors made during front-end design phases that could not be cost-effectively resolved during later design phases (Cooper 1988;Park et al 2021). Studies have also shown that the success of new products depends in part upon how well designers execute frontend design activities during product development (Khurana & Rosenthal 1998;Markham 2013).…”
Section: Front-end Design and Requirements Elicitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Park, Han, and Childs [9] revealed a broad review of specific studies on FFE that define the attributes and the structure of the performance related to the tasks, activities, and tools employed. The authors state six main FFE activities: opportunity identification, idea generation, requirements list, project mission definition, conceptual design, and prototyping tasks.…”
Section: Introductionmentioning
confidence: 99%